A teoria do impacto desproporcional e a desigualdade de sexo: como regras aparentemente neutras influenciam o trabalho, a família e a vida das mulheres - Coelho, Fabiana Moura (2023)
The present research dealt with the applicability of the disproportionate impact theory in cases involving gender inequality. The study starts on the concepts of sex and gender, defined as what is biologically observable, for sex, and a social construction that determines expectations related to sex, for gender. The premises of the disparate impact and the validity of the comparison with the United States were discussed. The disparate impact is defined as the proposal that intends to analyze the effects, on minority groups, of apparently neutral practices and policies. An impact that implies, in each practice, the inappropriate exclusion of groups belonging to protected categories (minorities), especially those related to sex, race or religion, is considered disparate. Cases in which a disparate impact in terms of sex on jurisprudence can be pointed out in chapter three. The cases are centered on matters of labor law, social security law and family law, in particular the Parental Alienation Law - no. 12.318/2010. The research concludes that the Brazilian Superior Courts have been sensitive to the issue of sex when explicitly confronted with it. The heart of the matter, at this point, is to highlight the cases in which gender inequality is not explicit and how to make this reflection reach the Courts. And it is in this context that the disparate impact can have a special contribution in Brazil, by highlighting aspects of how certain controversies can have a special impact on women.